Applied informatics : first International Conference, ICAI 2018, Bogotá, Colombia, November 1-3, 2018, Proceedings /: first International Conference, ICAI 2018, Bogotá, Colombia, November 1-3, 2018, Proceedings. (2018) - Unknown
No abstract available